Research on Optimization of a Solid Filling Mining Face Layout Based on a Combined Clamped Beam Model - Zhi-Yong Fu; Xu-Fei Gong; Peng-Fei Zhang; Cun-Wen Wang (Advances in Civil Engineering)
Optimizing the mining scheme is an essential work for improving recovery efficiency of filling mining. An optimization equation of mining face width under a gangue mining condition is derived firstly. Then, analysis of the optimization equation of the mining face width is carried out based on the measure data of the F5001 mining face in the Tangshan Coal Mine. At last, the reasonable mining face width is determined combined with numerical simulation. Results show that mining face width and roof subsidence increase with the increase of unit weight and mining depth, but decrease with the increase of the elastic modulus of roof. The maximum width of the mining face is 105 m in Tangshan Coal Mine. When the mining width increases from 66 to 105 m, the increasing percentage of roof subsidence is 15–18%. Roof subsidence is controlled less than 30% of the mining height. The variation range of the maximum roof subsidence is small, which means the mining face width can be designed reasonably through the proposed equation.